2000
DOI: 10.1128/iai.68.3.1102-1108.2000
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Activity of Coagulase-Negative Staphylococci in Bovine Mastitis

Abstract: Secreted toxins play important roles in the pathogenesis of bacterial infections. In this study, we examined the presence of secreted cytotoxic factors of coagulase-negative staphylococci (CoNS) from bovine clinical and subclinical mastitis. A 34-to 36-kDa protein with cell-rounding cytotoxic activity was found in many CoNS strains, especially in Staphylococcus chromogenes strains. The protein caused cell detachment and cell rounding in several cell lines, including HEp-2, Int 407, CHO-K1, and Y-1 cells. Nativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 42 publications
1
44
0
1
Order By: Relevance
“…At the species level, S. aureus has been traditionally considered the most common agent; however, recent studies have shown the increasing importance of S. epidermidis in bovine mastitis and have revealed that its incidence could be even higher than that of S. aureus (3,25,29). In fact, in the present study, 40% of the women carried S. aureus in their milk, while 60% of them harbored S. epidermidis isolates.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…At the species level, S. aureus has been traditionally considered the most common agent; however, recent studies have shown the increasing importance of S. epidermidis in bovine mastitis and have revealed that its incidence could be even higher than that of S. aureus (3,25,29). In fact, in the present study, 40% of the women carried S. aureus in their milk, while 60% of them harbored S. epidermidis isolates.…”
Section: Discussionmentioning
confidence: 54%
“…Traditionally, Staphylococcus aureus has been considered the main etiological agent, although Staphylococcus epidermidis is emerging as the leading cause in both human and veterinary medicine (3,25,29). Multidrug resistance to antibiotics and/or formation of biofilms is very common among clinical isolates of these two staphylococcal species; therefore, it is not strange that ca.…”
mentioning
confidence: 99%
“…Stepanović et al (2001) also showed strong proteolytic and DNase activities in 121 human and animal S. sciuri isolates. Zhang and Maddox (2000) stated that cytotoxic activity and casein hydrolysis activity of CNS from bovine mastitis was associated with production of 34-to 36-kDa protein. In this study, we also investigated esterase activity and we found the highest percentage of strains with this activity among S. epidermidis.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenicity of staphylococci is related to the production of several virulence factors responsible for the development of disease process ( factors were found in S. aureus strains isolated from bovine mastitis (Silva et al 2005, Hata et al 2006, Peles et al 2007, Melchior et al 2009, Capurro et al 2010, but only few studies involved search of virulence factors of CNS isolated from bovine mastitis (Zhang andMaddox 2000, Bochniarz andWawron 2012). Virulence factors of staphylococci have been investigated by measuring phenotypic expression of products associated with virulence (Taponen and Pyörälä 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation